The Influence of Religion in the Historiography of “World Civilization” - Petchvichit , Phanthip; Panitchayapan, Panadda (Interdisciplinary Academic and Research Journal, 2022)
The world since the scientific paradigm has been established as the dominant method to reach the knowledge, whereas religions were percept in opposition to science. However, this article dedicates to illustrating the problem of disenchantment in the historiography of World Civilization or World History. In the paper, I argue against the secularists who believe religions have been separated from the states and discouraged from the public sphere. This process began in the 19th century at the same time when the Western had constructed knowledge of the world through the study of World Civilization or World History that seemed substantial and natural. However, the World Civilization study is crucial to demonstrate the religious influence that has never declined from world politics since the Treaty of Westphalia in 1688, which secularists believed. As can be seen from the evolution of the World Civilization concept that marginalized the Late Antiquity history (the 3rd - 6th century) and the history of Muslims (the 7th - 15th century), both cases have been considered the periphery of the European Middle Ages. In this article, I analyze through the historiographical approach and post-secularism ideology to expose the consistent impact of religions on the World Civilization concept’s construction, even at that most significant time of secularism.